Beispiel Nr: 01
$ \text{Gegeben:}\\\text{Hypotenuse} \qquad c \qquad [m] \\ \text{Kathete}\qquad b \qquad [m] \\ \\ \text{Gesucht:} \\ \text{Kathete} \qquad a \qquad [m] \\ \\ a =\sqrt{c^{2} - b^{2} }\\ \textbf{Gegeben:} \\ c=15m \qquad b=12m \qquad \\ \\ \textbf{Rechnung:} \\ a =\sqrt{c^{2} - b^{2} } \\ c=15m\\ b=12m\\ a =\sqrt{(15m)^{2} - (12m)^{2} }\\\\a=9m \\ \small \begin{array}{|l|} \hline c=\\ \hline 15 m \\ \hline 150 dm \\ \hline 1,5\cdot 10^{3} cm \\ \hline 1,5\cdot 10^{4} mm \\ \hline 1,5\cdot 10^{7} \mu m \\ \hline 0,015 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline b=\\ \hline 12 m \\ \hline 120 dm \\ \hline 1,2\cdot 10^{3} cm \\ \hline 1,2\cdot 10^{4} mm \\ \hline 1,2\cdot 10^{7} \mu m \\ \hline 0,012 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline a=\\ \hline 9 m \\ \hline 90 dm \\ \hline 900 cm \\ \hline 9\cdot 10^{3} mm \\ \hline 9\cdot 10^{6} \mu m \\ \hline 0,009 km \\ \hline \end{array}\\$